Instructional Expertise and Micropolitics: The Social Networks of Instrumental Music Teachers. (October 2020) - Shaw, Ryan D.
The purpose of this study was to understand the social networks of three instrumental music teachers in a midwestern school district. Research questions were (1) How do instrumental music teachers describe their formal/instructional networks? and (2) How do instrumental music teachers' social networks differ by career stage? I used a qualitative ego network design to map social networks of information sharing with a focus on the flow of social capital. Data sources included a name-generating questionnaire to construct networks and two semistructured interviews focusing on the nature and significance of teachers' ties. Findings suggest that social networks showed particularities in terms of number of ties and tie strength. On matters of instruction, participants sought out music teachers whom they respected or who possessed specialized knowledge. Participants spoke of the importance of forging micropolitical ties to secure needs related to resources and scheduling, using ties strategically. Finally, participants felt that networks differed by career stage with advice seeking decreasing over time and networks becoming more close-knit. Implications are offered for music teachers and music teacher educators.